2018
DOI: 10.1007/s00429-018-1761-7
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and neurochemical characterization of the rostromedial tegmental nucleus (RMTg) in rats and mice

Abstract: The rostromedial tegmental nucleus (RMTg), also known as the tail of the ventral tegmental area (tVTA), is a GABAergic structure identified in 2009 that receives strong inputs from the lateral habenula and other sources, sends dense inhibitory projections to midbrain dopamine (DA) neurons, and plays increasingly recognized roles in aversive learning, addiction, and other motivated behaviors. In general, little is known about the genetic identity of these neurons. However, recent work identified the transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 51 publications
5
43
0
Order By: Relevance
“…Out of 151 recorded neurons, 59 were located in the RMTg, as defined by immunostaining for FOXP1 (Lahti et al, 2016; Smith et al, 2018) (Figure 2—figure supplement 1A,B). Consistent with previous studies that RMTg neurons encode motivational valence (Hong et al, 2011; Jhou et al, 2009), we found that RMTg neurons on average showed significant inhibition to reward cues during a time window 200–400 ms post-stimulus, and rapid excitations to all other phasic stimuli 0–100 ms post-stimulus (p < 0.0001 for all stimuli) (Figure 2B; Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of 151 recorded neurons, 59 were located in the RMTg, as defined by immunostaining for FOXP1 (Lahti et al, 2016; Smith et al, 2018) (Figure 2—figure supplement 1A,B). Consistent with previous studies that RMTg neurons encode motivational valence (Hong et al, 2011; Jhou et al, 2009), we found that RMTg neurons on average showed significant inhibition to reward cues during a time window 200–400 ms post-stimulus, and rapid excitations to all other phasic stimuli 0–100 ms post-stimulus (p < 0.0001 for all stimuli) (Figure 2B; Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we used endoscopic calcium imaging and selectively recorded RMTg neurons that project to either the VTA or the dorsal raphe nucleus (DRN), both of which are implicated in encoding of motivational stimuli (Cohen et al, 2012; Li et al, 2016). Because of the need to keep GRIN lenses short, this experiment was performed in mice, rather than rats, but the anatomy of the RMTg is very similar between species (Smith et al, 2018). We injected into wild type mice a retrogradely transported canine adenovirus expressing Cre recombinase (CAV2-Cre) into either the VTA or (in separate mice) the DRN, along with a second virus into the RMTg expressing a Cre-dependent fluorescent calcium indicator (gCaMP6f) (Figure 4A–C, Figure 4—figure supplement 1A,B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lateral habenula (LHb) has been implicated in processing aversive events across many species (Jhou et al, 2013; Matsumoto and Hikosaka, 2008; Salas et al, 2010; Stopper and Floresco, 2014; Wang et al, 2017). Neurons in the LHb are activated by negative motivational stimuli, which in turn suppress dopamine (DA) firing via activation of GABAergic neurons in the rostromedial tegmental nucleus (RMTg) (Brown et al, 2017; Hong et al, 2011; Jhou et al, 2009a; Jhou et al, 2009b; Ji and Shepard, 2007; Smith et al, 2019; Vento et al, 2017). Dysregulation of this pathway can lead to cognitive disorders associated with abnormal processing of motivational stimuli including depression (Baker et al, 2016; Elmer et al, 2019; Lawson et al, 2017; Shumake and Gonzalez-Lima, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…One such potential target is a small GABAergic region known as the rostromedial tegmental nucleus (RMTg), also known as the tail of the VTA (tVTA). First identified in 2009, the RMTg receives glutamatergic input from the lateral habenula (LHb), sends a dense projection to the VTA thereby exerting inhibitory control over midbrain dopamine neurons, and is delineated by expression of the transcription factor FoxP1 [25][26][27]. This neural circuit (LHb-RMTg-VTA), which exhibits only modest direct connectivity with the amygdala [28], has been characterized for its involvement in negative reward prediction error [29].…”
Section: Introductionmentioning
confidence: 99%